Effect of pregnancy planning on maternal and neonatal outcomes in women with Type 1 diabetes. Issue 9 (12th July 2017) - Wotherspoon, A. C.; Young, I. S.; Patterson, C. C.; McCance, D. R.; Holmes, V. A.; ,
Abstract: Aims: To assess the effect of pregnancy planning on maternal and neonatal outcomes in women with Type 1 diabetes. Methods: Pregnancy planning was assessed retrospectively in a cohort of women who participated in the Diabetes and Pre‐eclampsia Intervention Trial (DAPIT). Pregnancy planning was determined based on self‐report as to whether pregnancy was planned or unplanned. The effect of pregnancy planning on maternal and neonatal outcomes was examined, controlling for confounding variables. Results: A total of 747 women were included in the study, of whom 39% considered their pregnancy unplanned. Characteristics associated with unplanned pregnancy included being younger ( P <0.001), being a current smoker ( P <0.001), being from a lower social class ( P <0.001) and having higher HbA1c values prior to and throughout pregnancy ( P ≤0.005). Significantly fewer women with unplanned vs planned pregnancies received pre‐pregnancy counselling (24% vs 64%; P <0.001). Infants of women with unplanned pregnancies were more likely to be small for gestational age (<5 th centile; P =0.004), to be admitted to the neonatal care unit ( P =0.001) and to have a longer stay in hospital ( P =0.01). Outcomes did not differ between the groups in relation to pre‐eclampsia, congenital malformations or a composite adverse outcome. Conclusions: Risks associated with diabetes in pregnancy need to be highlighted to all women, their partners and families, and healthcare professionals. Further research is required to determine if these groups are fully aware of the risks associated with diabetes in pregnancy. What's new?: Being young, a smoker and from a lower social class were associated with unplanned pregnancy. Outcomes that were associated with unplanned pregnancy were very low birth weight and greater neonatal and maternal care requirements post‐delivery Poor preconception counselling rates among women who did not plan pregnancy suggests an urgent need for strategies to ensure all women receive preconception counselling, regardless of pregnancy intention.